Examining the Driving Forces Affecting Energy Intensity during Financial Crisis: Evidence from ASEAN-6 Countries - Setyawan, Dhani; Dyarto, Rakhmin; Setiawan, Hadi; Tenrini, Rita Helbra; Damayanty, Sofia Arie (International Journal of Energy Economics and Policy, 2020)
This study observes the factors affecting the changes of energy intensity in Indonesia and five selected ASEAN countries during the period (1971 to 2016) particularly measuring its impact during 1997 financial crisis. By employing the Logaritmic Mean Divisia Index, this study summaries that the changes in energy intensity in the ASEAN-6 economies was a result of the changes within industry energy intensity (intensity effect). The intensity effects also provide a proxy measure of energy efficiency activity at the sectoral level. Overall, the general direction of the intensity effect in all ASEAN countries is downward. These decreasing intensity effects show that the trend towards technological changes in ASEAN countries has assisted significantly in increasing energy efficiency. Further, all the ASEAN-6 countries showed a change in the structure index indicates that the structure of economy periodically shifted away from less energy intensive sector to more energy intensive sector. Keywords: Energy Efficiency, ASEAN countries, Energy Intensity, Indonesia. JEL Classifications: Q43, O13, O11 DOI: https://doi.org/10.32479/ijeep.9565